Holistic Approaches to Employee Growth and Performance Improvement - Korwa, Irma Adelina; Ibrahim, Muhdi B. Hi; Irawan, Andri; Yendra, Yendra; Lina, Ros (Advances: Jurnal Ekonomi & Bisnis, 2024)
The purpose of this study is to examine the holistic approaches to employee growth and performance improvement within organizational contexts. It explores the interconnectedness of individual, team, and organizational factors in fostering comprehensive employee development. The research design and methodology involve a qualitative literature review, systematically examining existing scholarly works to gain insights into effective strategies for enhancing employee effectiveness and capability. Findings and discussion highlight the significance of integrating diverse dimensions of employee development, including skill enhancement, psychological well-being, and organizational culture. Implications for practice underscore the importance of adopting integrated approaches that address various facets of employee growth, such as investing in ongoing learning and development initiatives, implementing supportive organizational practices, and nurturing leadership capabilities. These findings have implications for organizational leaders and practitioners seeking to enhance performance and foster employee well-being in today's dynamic work environments.